Physicochemical Properties of Herbal Tea Bags from Belimbing Wuluh Leaves (Averrhoa bilimbi) and Gotu Kola Leaves (Centella asiatica) with the Addition of Cinnamon Powder (Cinnamomun burmanii) - Diana Sylvi; Daimon Syukri; Fachrur Rozi; Devi Purnama Sari (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2022)
This study aims to study the characteristics of herbal teabags from belimbing wuluh leaves and gotu kola leaves with the addition of cinnamon powder. This study used a completely randomized design with 5 treatments, namely differences in the addition of cinnamon powder 0%, 1%, 2%, 3% and 4% with 3 replications. The data obtained were analyzed statistically using ANOVA (Analysis Of Variance) and if they were significantly different, then continued with the DNMRT (Duncan's News Multiple Range Test) test at 5% level. The results showed that the level of addition of cinnamon powder had a significant effect on antioxidant activity, total water soluble ingredients, total polyphenols, color, taste, and flavor. Differences in the substitution level of cinnamon powder had no significant effect on water content and pH. The best treatment in this study was treatment E with the addition of 4% cinnamon powder, the organoleptic results obtained were the average value of color preference 3.95 (like), taste 3.65 (like), and flavor 4 (like). The results of chemical analysis on tea products are water content 7.88%, total polyphenols 109.32 mg GAE/g, IC50 value 96.71, total water soluble ingredients 19.66% and in steeped tea pH value is 6.13, and activity antioxidant 36.93%.